(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the question of the connection of foreign language teaching methodology with other subjects was discussed. It was also researched that methodology has its own history due to the establishment of its status as a science. The connection of the methodology with linguistics, then with psychology, and finally with pedagogy or even with several other disciplines was noted